The Determinants of Tax Avoidance in Indonesian Banking Companies - Puspita, Priska Ane; Nurlaela, Siti; Dewi, Riana Rachmawati (Universitas Tidar, 2025)
This study intends to investigate the incentives of banking companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023 involved in tax avoidance. The possible predictive factors examined in this study include firm size, leverage, independent commissioners, and profitability. This study relies on a quantitative approach using secondary data obtained from the company’s financial statements, which are available on the website of IDX or the company’s website. The sample was chosen using a purposive sampling technique, resulting in 30 companies (89 observations). Data analysis was conducted using multiple linear regression with the assistance of SPSS. Based on the hypothesis testing result, this study unveils that firm size and independent commissioners have a negative effect on tax avoidance, while profitability has a positive effect on tax avoidance. Meanwhile, leverage does not affect tax avoidance in Indonesian banking companies. The result of this study implies that larger companies or higher independent commissioners tend to comply more with tax regulations, thus avoiding tax avoidance practices. On the other hand, more profitable companies tend to engage in tax avoidance practices to minimize their tax payment